Cocrystal trimorphism as a consequence of the orthogonality of halogen- and hydrogen-bonds synthons. Issue 93 (6th November 2019) - Topić, Filip; Lisac, Katarina; Arhangelskis, Mihails; Rissanen, Kari; Cinčić, Dominik; Friščić, Tomislav
Abstract : Trimorphic cocrystals, i.e. multi-component molecular crystals with three polymorphic structures, are exceedingly rare. First example of a trimorphic halogen-bonded cocrystal, reported here, shows a critical role for the interaction orthogonality. Abstract : True trimorphic cocrystals, i.e. multi-component molecular crystals of identical composition that exhibit three polymorphic structures, are exceedingly rare and so far no halogen-bonded cocrystal system has been reported to exhibit trimorphism. Here we describe a unique example of a trimorphic cocrystal exhibiting both hydrogen and halogen bonds in which the differences between polymorphs reveal their orthogonality, evident by the apparently independent variation of well-defined hydrogen- and halogen-bonded motifs.